1981
DOI: 10.1038/clpt.1981.216
|View full text |Cite
|
Sign up to set email alerts
|

Verapamil kinetics in normal subjects and patients with coronary artery spasm

Abstract: Verapamil kinetics after intravenous and single and long-term oral dosing were studied in 12 patients with coronary artery spasm and four normal subjects. The decline in plasma concentration after intravenous doses was described by triexponential decay equation, with a terminal half-life (t1/2) of 5 hr. After a single oral dose the bioavailability was only 24%, probably because of the first-pass metabolism. During long-term oral doses of 80 mg every 6 hr, mean peak and trough concentrations were 255 +/- 90 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
40
2

Year Published

1983
1983
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(52 citation statements)
references
References 3 publications
10
40
2
Order By: Relevance
“…In patients, repeat dosing has led to a significant increase in the plasma verapamil halflife (Freedman et al, 1981;Shand et al, 1981;Schwartz et al, 1982). Both formulations led to an increase in verapamil AUC on repeat dosing and it has been suggested that this effect results from impaired clearance or, less likely, a further distribution of verapamil into deeper tissue compartments during repeat dosing .…”
Section: Discussionmentioning
confidence: 99%
“…In patients, repeat dosing has led to a significant increase in the plasma verapamil halflife (Freedman et al, 1981;Shand et al, 1981;Schwartz et al, 1982). Both formulations led to an increase in verapamil AUC on repeat dosing and it has been suggested that this effect results from impaired clearance or, less likely, a further distribution of verapamil into deeper tissue compartments during repeat dosing .…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon may contribute significantly to the considerable interindividual variation in CYP3A-based drug interactions. Second, verapamil itself is a CYP3A substrate, and upon repeated dosing, autoinhibition results in increases in oral bioavailability and decreased systemic clearance (Freedman et al, 1981;Eichelbaum and Somogyi, 1984). Thus, clinical responses, both desirable (e.g., blood pressure lowering and heart rate control) and undesirable (e.g., hypotension and heart block), may differ between CYP3A5 expressers and nonexpressers.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is consistent with several literature reports demonstrating the association between inhibitory metabolites and time-and dose-dependent pharmacokinetic alterations. Propranolol (Wood et al, 1978; Narimatsu et al, 2001), verapamil (Freedman et al, 1981;Shand et al, 1981;Ma et al, 2000;Wang et al, 2004), and diltiazem (Höglund and Nilsson, 1989;Ma et al, 2000;Yeo and Yeo, 2001) all form metabolites capable of MBI, and exhibit time-dependent increases in exposure after multiple dosing. Whereas in vitro data suggest that inhibition of CYP3A by M2 is the most probable cause for the time-dependent pharmacokinetics, the hypothesis has to be considered in the context of the low plasma exposures of this metabolite (Table 3).…”
Section: Discussionmentioning
confidence: 99%